Interdisciplinary studies are an entry to the development of psychological and educational research - (the establishment of startups and inventions in Algeria) - Aicha LAIDI (Social Sciences Journal, 1970)
The scientific research in Algerian higher education institutions is facing competitive challenges stemming from the characteristics of the society to which it belongs, as a result of the witnessed developments in the recent period in various economic and social sectors, which insisted on using technology, innovation, creativity, and the transformation into a fourth-generation university. In order to enhance the outputs of the university and to generalize the benefit from the student and the professor to society, and reaching new solutions for phenomena that require invention in aspects where old solutions have failed.And because establishing startups and the patent in scientific research have become the reflective mirror of the originality of various scientific researches, we sought through this study to do an analytical approach about what interdisciplinary studies provide for psychology and educational sciences research in their integration with other sciences, of development that leads them to the establishment of startups and patents. The study concluded that psychology and educational sciences research are among the fertile studies that are capable of being integrated with other studies as well as openness to spaces of creativity and advancement by establishing startups, with the existence of obstacles limiting this research integration, represented in placing these studies among theoretical research, as well as the weakness of the culture of innovation and entrepreneurship in psychological and educational research